WALKTHROUGH SUPERVISION AS A COLLABORATIVE SUPERVISION INNOVATION: A STUDY ON ENHANCING THE QUALITY OF LEARNING PRACTICES - Hariyati, Nunuk; Khamidi, Amrozi; Wulandari, Ayu; Islamiah, Nia; Nashrullah, Mochamad; Purwoko, Lukman Fajar; Abdullah (Academic Journal Research, 2025)
Objective: This study aims to analyse the implementation of walkthrough supervision as a collaborative supervision strategy in improving the quality of learning practices at junior and senior high school levels. Method: This research was conducted using a qualitative approach with a multi-case study design. Data were collected through direct observation, in-depth interviews with principals, teachers and supervisors, and analysis of supervision documents. The analysis process was conducted thematically to identify implementation patterns, challenges, and improvement strategies that emerged from the practice of walkthrough supervision in improving the quality of learning practices at the junior and senior high school levels at Yayasan Nurul Fikri Bina Generasi Bogor.  Results:  The results showed that walkthrough supervision in junior and senior high school of NFBS Bogor is implemented systematically through five stages by emphasising learning authenticity, continuous reflection, and teacher-supervisor collaboration. Obstacles such as time constraints, competency variations, supervisor inconsistency, and cultural factors are overcome through adaptive strategies, so that challenges actually strengthen collaboration. This supervision has an impact on improving teaching skills, classroom management, student engagement, as well as fostering a continuous reflective culture. This model has the potential to be adapted in other schools with adjustments to the vision, culture, teacher competencies and structural support.  Novelty: The innovation of this research lies in the transformation of walkthrough supervision into a collective reflective culture, the collaborative role of teachers-supervisors, and adaptive strategies to face obstacles. This model not only improves teacher competence and classroom culture, but also has the potential to be replicated with adjustments to the school context.